Perencanaan Pemasaran Pendidikan dalam Menarik Minat Peserta Didik Baru di SMP Islam Cendikia Faiha Palembang - Nadilla, Venda; Setyaningsih, Kris; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the increasing competition among educational institutions, particularly in the city of Palembang, which compels schools to develop effective marketing strategies in order to maintain their existence and increase the number of new student enrollments each year. The aim of this study is to describe the planning of educational marketing in attracting new students at SMP Islam Cendikia Faiha Palembang. This study employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The informants in this study consist of the principal as the key informant, as well as the vice principal for curriculum and teachers as supporting informants. The data analysis technique involves data collection, data presentation, verification, and conclusion drawing. The results of the study show that the educational marketing planning at SMP Islam Cendikia Faiha Palembang is carried out through four main stages: determining the targets and objectives for new student admissions, formulating the current condition of the school, identifying internal strengths and obstacles, and developing a strategic plan to achieve the set goals. The strategies implemented include promotion through social media, brochure distribution, collaboration with elementary schools, and organizing open house events. The entire planning process is conducted collaboratively and participatively, involving the principal, foundation, teachers, and school staff.